Corrosion behavior of 904L austenitic stainless steel in hydrofluoric acid. Issue 5 (12th January 2018) - Zou, Guobo; Shi, Wei; Xiang, Song; Ji, Xuanming; Ma, Guoqiang; Ballinger, R. G.
Abstract : An insoluble layer is deposited on 904L in HF due to a preferential reaction between [F − ] and the [Ni] from the alloy. This insoluble deposit layer helps isolate the aggressive ions from the base metal, while inhibits the passivation of 904L in HF. Abstract : Corrosion behaviors of 904L austenitic stainless steel in HF and HCl were studied and compared using electrochemical method, microscopic analysis, and phase analysis. An insoluble layer is deposited on 904L in HF due to a preferential reaction between [F − ] and the [Ni] from the alloy. This insoluble deposited layer not only helps isolate the aggressive ions from the base metal, but also inhibits the passivation of 904L in HF, the mechanism for which was entirely different from that in HCl.